PERAN DIALOG INTERAKTIF BERBASIS MEDIA SOSIAL DALAM MENINGKATKAN KUALITAS KOMUNIKASI INTERPERSONAL GURU DAN SISWA - Sahreza Kalijunjung Pangaribuan; Natalie Natasya Pardede (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2026)
This study examines the role of interactive dialogue based on social media in enhancing the quality of interpersonal communication between teachers and students. The rapid development of digital technology has transformed educational communication patterns from conventional one-way interaction into more open, fast, and participatory communication. In this context, social media functions not only as an information medium but also as an interactive space that enables more intensive two-way communication between teachers and students. This research employs a qualitative approach using a library research method to analyze various concepts, theories, and previous studies related to interpersonal communication and the use of social media in education. The focus of the study is directed toward how interactive dialogue facilitated by social media can improve openness, trust, emotional closeness, and the effectiveness of message delivery in the learning process. The findings indicate that interactive dialogue based on social media plays a significant role in strengthening interpersonal relationships between teachers and students. Social media enables more flexible communication that is not limited by time and space, while also encouraging active student participation in learning activities. Furthermore, the quality of interpersonal communication improves through the creation of more egalitarian, responsive, and collaborative communication environments.